Phản ứng oxi hóa phenol trên điện cực SnO2-Sb2O5/Ti - Mai Thanh, Đinh Thị; Lê Hiền, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The 0.01 M phenol + H2SO4 0.5 M oxydation process on SnO2-Sb2O5/Ti anode electrode is researched by cyclic voltammetry and elctrochemical impedance methods. The results show that phenol oxydation potential is 1.2 V/SCE (less than water oxydation potential). This is favourable condition for the phenol oxydation reaction with a high efficiency. The phenol decomposed efficiency at 10 mA/cm2 imposed current during 7 hours is 39% but the COD removal (%) is 62.7%.